Effects of the synthetic method on the particle size and purity of magnetite - Jaramillo-Tabares, Beatriz; Zuleta-Gil, Alejandro Alberto; Jaramillo-Isaza, Franklin (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
The characterization of magnetites synthesized by methods reported with some modifications is presented. The influence on purity and particle size of the obtained oxides is discussed. The samples were characterized by Mössbauer Spectroscopy at room temperature, particle size analysis by light scattering and by transmission electron microscopy of naked particles. The results showed that depending on the method of synthesis there are variations on stoichiometry and composition of magnetites, being this difference more important when the rate of addition of the alkaline solution to the combined ferrous and dispersant solution is changed. Moreover, it has been found strong agglomeration evidenced by TEM, however the sizes of the individual crystallites are in the nanometer scale.